Current Status of Bovine Tuberculosis in Otukpo, Nigeria (2014)
We conducted a study to determine both the retrospective and current prevalences of bovine tuberculosis (BTB) among cattle slaughtered in Otukpo abattoir, Benue State. Retrospective data of BTB cases detected between the year 2010 and 2012 were collected and collated from the abattoir records of the Ministry of Agriculture and Natural Resources, Makurdi, Benue State, Nigeria. Furthermore, gross lesions suggestive of BTB collected during routine meat inspection from slaughtered cattle at the Otukpo abattoir over a period of four months were processed using Ziehl-Neelsen microscopy (ZNM). Data obtained were analysed using SPSS version 17.0 for windows. The results showed a BTB prevalence of 2.9% retrospectively with no significant difference (p>0.05) between the prevalence and seasons of the year. Furthermore, out of 248 pathological lesions suggestive of BTB collected, a prevalence of 6.5% was recorded by the Ziehl-Neelsen microscopy (ZNM). In addition, the cows (4.8%) were more affected than bulls (1.6%).There was also a significant association between BTB prevalence and body condition scores (p < 0.05) of the cattle screened. Our findings show that BTB is endemic in cattle slaughtered in Otukpo abattoir, and portends potential for zoonotic transmission especially abattoir workers and consumers. There is the need to strengthen routine meat inspection of slaughtered animals in the study area and in Nigeria as a whole in order to safeguard the health of meat consumers. Stepping up Public Health awareness on zoonotic tuberculosis among abattoir workers is also advocated.